Pengaruh Motif Penggunaan Media terhadap Intensitas Mendengarkan Podcast (Survei Eksplanatori Motif Penggunaan Media terhadap Intensitas Mendengarkan Podcast pada Platform Noice) - Muhammad Irfan Maulana; Atwar Bajari; Kunto Adi Wibowo (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This research aims to determine the extent of the influence of media usage motives. This study employs a quantitative approach with an explanatory survey method aimed at obtaining explanations regarding the causal relationships between the research variables, conducted through inferential statistical testing using multiple linear regression. The sample was 162 samples. The results of the study indicate that the variables of entertainment motives, information-seeking motives, and platform superiority motives have a significant effect on the intensity of podcast usage on the Noice platform. Meanwhile, time-passing motives, affiliation motives, self-discovery motives, and social interaction motives do not have a significant effect but contribute positively to the intensity of podcast usage on the Noice platform. The conclusion of this study is that there is an influence of media usage motives on the intensity of podcast usage on the Noice platform.